Environmental toxicity of nanomaterials - Dasgupta, Nandita; Ranjan, Shivendu; Kumar, Vineet; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
Environmental Toxicity of Nanomaterials focuses on causes and prevention of environmental toxicity induced by various nanomaterials. In sixteen chapters it describes the basic principles, trends, challenges, and future directions of nanoecotoxicity. Environmental Toxicity of Nanomaterials introduces nanoecotoxicity, describes various factors affecting the toxicity of nanomaterials, discusses various factors that can impart nanoecotoxicity, reviews various studies in the area of nanoecotoxicity evaluation, and describes the safety and risk assessment of nanomaterials. In addition, the book discusses strategies for mitigating nanoecotoxicity. Lastly, the authors provide guidelines and protocols for nanotoxicity evaluation and discuss regulations for safety assessment of nanomaterials. In addition to environmental toxicologists, this book is aimed at policy makers, industry personnel, and doctoral and postdoctoral scholars.The future acceptance of nanomaterials in various industries depends on the impacts of nanomaterials on the environment and ecosystem. This book analyzes the safe utilization of nanotechnology so the tremendous prospect of nanotechnology can be achieved without harming either living beings or the environment.
chapter 1 Toxic Effects of Nanomaterials on Environment / Rajeev Kumar -- chapter 2 Nanotoxicity: Impact on Health and Environment / Ponnala Vimal Mosahari -- chapter 3 Nanotoxicological Evaluation in Marine Water Ecosystem: A Detailed Review / Anna Giulia Cattaneo -- chapter 4 Interaction of Carbon Nanomaterials with Biological Matrices / S. Gajalakshmi -- chapter 5 Interaction of Inorganic Nanoparticles with Biological Matrices / Priya Sharma -- chapter 6 Effects of Engineered Nanoparticles on Bacteria / Changjian Xie -- chapter 7 Comparative Risk Assessment of Copper Nanoparticles with Their Bulk Counterpart in the Indian Major Carp Labeo rohita / Kaliappan Krishnapriya -- chapter 8 Toxic Effects of Nanomaterials to Plants and Beneficial Soil Bacteria / Shiwani Guleria -- chapter 9 Nanotoxicity of Silver Nanoparticles: From Environmental Spill to Effects on Organisms / Kevin Osterheld -- chapter 10 Nanotoxicity on Human and Plant Pathogenic Microbes and Aquatic Organisms / Akhilesh Dubey -- chapter 11 Methods of In Vitro and In Vivo Nanotoxicity Evaluation in Plants / Ilika Ghosh -- chapter 12 In Vitro and In Vivo Nanotoxicity Evaluation in Plants / Homa Mahmoodzadeh -- chapter 13 Phytochemicals and Their Functionalized Nanoparticles as Quorum Sensing Inhibitor and Chemotherapeutic Agent / Brajesh Kumar -- chapter 14 Nanotoxicological Evaluation in Freshwater Organisms / Lindsey C. Felix -- chapter 15 Guidelines and Protocols for Nanotoxicity Evaluation / Bindu Sadanandan -- chapter 16 Regulations for Safety Assessment of Nanomaterials / Preetika Biswas.
Keywords: Environmental toxicology; Nanostructures -- toxicity; Natural disasters; MEDICAL / Pharmacology; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Environmental / General; Carbon Nanomaterials; Ecotoxicology; Engineered Nanoparticles; Inorganic Nanomaterials; Marine Ecosystem; Nanotoxicology